Poor nutritional status based on controlling nutritional status score and nutritional risk index may be related to the occurrence of complications after laparoscopic treatment in patients with gastrointestinal tumors aged no more than 60 years - Deng, Xueyong; Li, Zhiwang; Ye, Lv; Yang, Chengkun (Frontiers in Oncology, 2025)
BackgroundNutritional status is related to the postoperative complications in gastrointestinal tumors. Early-onset and late-onset tumors have differences in molecular characteristics and clinical manifestations. The purpose of this study is to explore the relationship between preoperative nutritional assessment indices (prognostic nutritional index (PNI), nutritional risk index (NRI), and controlled nutritional status (CONUT) score) and the occurrence of complications after laparoscopic treatment in patients with gastrointestinal tumors aged ≤60 years.Methods1405 patients with gastrointestinal tumors aged ≤60 years who underwent laparoscopic surgery were retrospectively analyzed. Medical records (age, gender, body mass index (BMI), hypertension, diabetes mellitus, tumor location, preoperative laboratory test results, imaging results, complications) were collected. The relationship between PNI, NRI, CONUT and postoperative complications were analyzed.ResultsThere were 584 (41.6%) patients with postoperative complications and 821 (58.4%) without. The distribution of CONUT grade and the means PNI and NRI were significant differences between the two groups (all p<0.001). When postoperative complication was set as the endpoint of PNI and NRI, the cutoff value of PNI and NRI was 43.425 and 100.045, respectively. Logistic regression analysis showed that low NRI level (<100.045 vs. ≥100.045) (odds ratio (OR): 1.863, 95% confidence interval (CI): 1.377-2.522, p < 0.001), abnormal CONUT score (OR: 1.333, 95% CI: 1.002-1.772, p = 0.048) were significantly associated with postoperative complications.ConclusionsLow NRI level, abnormal CONUT score, underweight, and intestinal tumor were significantly associated with postoperative complications in gastrointestinal tumors patients with aged ≤ 60 who performed laparoscopic surgery.